Concept and classification of public services - Rakhmanov Zafarjon Zayniddinovich (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
This article analyzes the concept and classification of public service. The opinions of scientists and specialists on civil service were discussed. The experience of national and foreign countries in the provision of public services is analyzed. Proposals and recommendations for solving problems related to the industry are given.